1990
DOI: 10.3109/02841869009096396
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing Sertoli Cell Tumours of the Human Testis—a Report of Two Cases and a Review of the Literature

Abstract: The median time to progression was 16 weeks for patients receiving doxorubicin and 5-FU and 24 weeks for patients receiving doxorubicin and ftorafur. This difference was not statistically significant. There was no significant difference in survival between groups I and 11. The median survival was 16 weeks for patients receiving doxorubicin and 5-FU and 25 weeks for patients receiving doxorubicin and ftorafur (Figure).Discussion. The non-haematological toxicity was very similar in the two treatment regimens. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The value of surgery for patients with large‐volume or widespread, metastatic disease appears to be limited. In our series as well as in other reports,3, 10 RPLND and surgery for metastatic disease in other sites seemed to provide effective local treatment. Most patients, however, eventually succumbed to widespread recurrence.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The value of surgery for patients with large‐volume or widespread, metastatic disease appears to be limited. In our series as well as in other reports,3, 10 RPLND and surgery for metastatic disease in other sites seemed to provide effective local treatment. Most patients, however, eventually succumbed to widespread recurrence.…”
Section: Discussionsupporting
confidence: 81%
“…These patients developed evidence of retroperitoneal disease 14–58 months after orchiectomy and had clinical Stage II–III disease at the time they underwent RPLND. Although most metastases of sex cord–stromal tumors are detected at the time of diagnosis or within 1 year of orchiectomy, a number of studies also report the appearance of metastatic disease as late as 9 years3 and 15 years10 after orchiectomy, suggesting the presence of clinically undetected metastatic disease with variable growth and progression potential. Although the therapeutic impact of RPLND in patients with small‐volume metastatic retroperitoneal disease is unclear, it is reasonable to assume that, if RPLND has a therapeutic benefit, then such a benefit would be greater in patients who have small‐volume retroperitoneal metastasis (defined as clinical Stage ≤ IIA or pathologic Stage IIA: metastasis with a lymph node mass measuring ≤ 2 cm in greatest dimension or ≤ 5 positive lymph nodes, with none measuring > 2 cm in greatest dimension) compared with patients who have large‐volume disease.…”
Section: Discussionmentioning
confidence: 99%
“…106 In general, high radiation doses (40 Gy) have been recommended. In a review of metastasizing Sertoli cell tumors, Madson and Hultberg reported that irradiation of para-aortic lymph nodes may provide effective local treatment.…”
Section: Radiotherapymentioning
confidence: 99%
“…Metastatic spread of this tumor occurs mostly to the lymphatics [6], However, organ métastases such as liver, lung and bone were also reported [4], As the condition is rare, all institutions tried their own treatment protocol for their patients [4,7,8], By now, no unique approach has been reported to be uniformly successful. RPLND, as aggressive local treatment, was reported to have a favor able effect on survival [3,7,8], For those patients with residual disease, platinum-based chemotherapy was re ported to have some favorable effect especially for sub types other than Leydig cell tumor [3,4,[7][8][9], As the con dition is rather different than germ cell tumors of the tes tis, the chemotherapy combination used and reported to be successful by Athanassiou et al [3] became our prefer ence.…”
mentioning
confidence: 99%
“…RPLND, as aggressive local treatment, was reported to have a favor able effect on survival [3,7,8], For those patients with residual disease, platinum-based chemotherapy was re ported to have some favorable effect especially for sub types other than Leydig cell tumor [3,4,[7][8][9], As the con dition is rather different than germ cell tumors of the tes tis, the chemotherapy combination used and reported to be successful by Athanassiou et al [3] became our prefer ence. Patients with advanced disease at diagnosis usually had a poor prognosis [6][7][8]. Our very limited experience of treating metastasized gonadal stromal tumor with RPLND followed by platinum-based chemotherapy regi men was not encouraging although the histopathology was Sertoli cell dominating.…”
mentioning
confidence: 99%